2018
DOI: 10.1111/cmi.12952
|View full text |Cite
|
Sign up to set email alerts
|

PE_PGRS3 ofMycobacterium tuberculosisis specifically expressed at low phosphate concentration, and its arginine-rich C-terminal domain mediates adhesion and persistence in host tissues when expressed inMycobacterium smegmatis

Abstract: PE_PGRSs of Mycobacterium tuberculosis (Mtb) represent a family of complex and peculiar proteins whose role and function remain elusive. In this study, we investigated PE_PGRS3 and PE_PGRS4, two highly homologous PE_PGRSs encoded by two contiguous genes in the Mtb genome. Using a gene-reporter system in Mycobacterium smegmatis (Ms) and transcriptional analysis in Mtb, we show that PE_PGRS3, but not PE_PGRS4, is specifically expressed under low phosphate concentrations. Interestingly, PE_PGRS3, but not PE_PGRS4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 82 publications
0
33
0
Order By: Relevance
“…37 Aggregation masks the GO blades and cations act as "bridges" between the negatively charged GO surface and the mycobacterial surface, which is also negatively charged. 38 In a series of experiments, we also showed that treatment with GO impairs mycobacterial entry into macrophages. Interestingly, GO was able to reduce the intracellular mycobacterial load as demonstrated by CFU analysis and confocal microscopy by trapping extracellular mycobacteria.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…37 Aggregation masks the GO blades and cations act as "bridges" between the negatively charged GO surface and the mycobacterial surface, which is also negatively charged. 38 In a series of experiments, we also showed that treatment with GO impairs mycobacterial entry into macrophages. Interestingly, GO was able to reduce the intracellular mycobacterial load as demonstrated by CFU analysis and confocal microscopy by trapping extracellular mycobacteria.…”
Section: Discussionmentioning
confidence: 84%
“…Six hours post incubation colony forming units (CFUs) were determined by plating serial dilutions of the suspensions on 7H11 solid medium (Difco) supplemented with 10% Oleic Albumin Dextrose Catalase (OADC) (Sigma-Aldrich). 38 To measure the GO trapping effect, suspensions of mycobacteria/GO were sonicated in a water bath (Becton Dickinson, output puissance 100 W to 42 kHz AE6%) for different time points (5 0 and 20 0 ) and the CFU was determined as above.…”
Section: In Vitro Antimicrobial Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Farhat et al detected four different variants in PE-PGRS9 appearing and disappearing over time (25), while the variant T320A emerged over the time of 9 months in another study (51). PE-PGRS3 has been found to be specifically expressed at low phosphate concentrations, and its unique, arginine-rich C-terminal domain was suggested to enhance adhesion and to be involved in tuberculosis pathogenesis (66).…”
Section: Comparison Of Microevolved Loci Between Studiesmentioning
confidence: 99%
“…PPE37 was induced under low-iron conditions through the course of infection (Ahmad et al, 2018). PE_PGRS3 is specifically expressed under low phosphate concentrations (De Maio et al, 2018). In contrast, transcriptome data revealed that PE35 was significantly reduced under persistence conditions (Boshoff et al, 2004).…”
Section: Introductionmentioning
confidence: 98%